Evaluation of the Physical Stability of a Grape Seed Oil Nanoemulsion Base Using a Centrifugation Test - Siti Ruqaiyah Lakoro; Teti Sutriyati Tuloli; Mohamad Aprianto Paneo; Robert Tungadi; Ariani H Hutuba (Jurnal Literasi Mandiri, 2026)
Nanoemulsions are nanometer-scale dispersion systems used as bases for pharmaceutical and cosmetic preparations because they can improve the solubilization and physical stability of lipophilic ingredients. This study evaluated the physical stability of a grape seed oil nanoemulsion base containing Tween 80, PEG 400, Poloxamer 407, and Transcutol HP using an accelerated centrifugation test. Four formulations with different surfactant and co-surfactant concentrations were prepared and centrifuged at 2,000, 4,000, 6,000, and 8,000 rpm. Homogeneity, clarity, turbidity, and phase separation were assessed visually after each treatment. All formulations remained homogeneous without visible phase separation at 2,000 and 4,000 rpm. At 6,000 rpm, several formulations showed increased turbidity but no phase separation. At 8,000 rpm, the formulations remained homogeneous and showed no visible phase separation. The stability of the system may be associated with Tween 80 reducing interfacial tension, PEG 400 and Transcutol HP supporting solubilization of the oil phase, and Poloxamer 407 providing steric stabilization. These results demonstrate satisfactory physical stability under the applied centrifugation conditions and support further evaluation through droplet-size analysis, polydispersity index, zeta potential, rheology, and long-term storage studies.